Praefiguratio: Exemplary History and Temporal Order in the Thirtieth Anniversary of the First Hungarian Soviet Republic of 1919 - Apor, Péter (Politics, religion & ideology, 2011)
Postwar Hungarian Communists wanted to construct the history of 1919 as an instance of a usable past and establish the First Hungarian Soviet Republic as the praefiguratio of their own regime. In this attempt they could benefit from previous Soviet exercises in historical typology, which identified episodes in the past as models for contemporary political action. Nonetheless, the thirtieth anniversary of the Hungarian Bolshevik regime in 1919 was not only an occasion for creating a historical interpretation adequate for the objectives of Sovietization. The ceremonies did not merely aim at making their conception of history authentic, but also to induce a particular politicized relationship to historical time. Yet, the ceremonies Hungarian Communists carefully designed to disseminate their political agenda failed in fulfilling these goals. Their failure calls the attention to that the relationship of cautiously executed political rituals and the credibility of ideological messages is far from being unambiguous. The case of the thirtieth anniversary of First Hungarian Soviet Republic provides the opportunity to examine how historical festivals function and what are the criteria of successful political rituals.